Lectotypifications in Manihot sect. Graciles (Euphorbiaceae) - Melo, Talita Merieli Silva De; Da Silva, Marcos José; Oliveira, Luciana Dos S. Dias De; Santos, Leidiana Lima Dos; Sales, Margareth Ferreira De (Phytotaxa, 2017)
During a revisional and phylogenetic study of Manihot sect. Graciles, 400 vouchers were assessed, including type and historical collections, as well as protologues, and some typification problems were found in certain taxa. Therefore, ten lectotypes are herein proposed.